Combating poverty and inequality : structural change, social policy and politics - Bangura, Yusuf, 1950- (United Nations Research Institute for Social Development, 2010)
Proposes a sustainable and inclusive development strategy to reduce seemingly intractable poverty and inequality based on: generation of jobs that are adequately renumerated and accessible to all, comprehensive social policies grounded in universal rights and supportive of change and democratic politics, and ensuring that states are responsive to citizen needs and that the poor have influence on policy-making.